Diagnostic power of diffusion-weighted magnetic resonance imaging for the presence of lymph node metastasis: a meta-analysis - Kong, Xiang-chuang; Gazyakan, Emre; Engel, Holger; Kneser, Ulrich; Hirche, Christoph (Journal of Huazhong University of Science and Technology. Medical sciences, 2017)
SummaryPresent work was designed to quantitatively evaluate the performance of diffusion-weighted magnetic resonance imaging (DWI) in the diagnosis of the presence of metastasis in lymph nodes (LNs). Eligible studies were identified from systematical PubMed and EMBASE searches. Data were extracted. Meta-analyses were performed to generate pooled sensitivity and specificity on the basis of per-node, per-lesion and per-patient, respectively. Fourteen publications (2458 LNs, 404 lesions and 334 patients) were eligible. Per-node basis demonstrated the pooled sensitivity and specificity was 0.82 (P<0.0001) and 0.90 (P<0.0001), respectively. Per-lesion basis illustrated the pooled sensitivity and specificity was 0.73 (P=0.0036) and 0.85 (P<0.0001), respectively. Per-patient basis indicated the pooled sensitivity and specificity was 0.67 (P=0.0909) and 0.86 (P<0.0001), respectively. In conclusion, DWI has rather a negative predictive value for the diagnosis of LN metastasis presence. The difference of the mean apparent diffusion coefficients between benign and malignant LNs is not yet stable. Therefore, the DWI technique has to be further improved.